let K be Field; :: thesis: for n being Nat
for M1 being Matrix of n,K holds (- M1) @ = - (M1 @)

let n be Nat; :: thesis: for M1 being Matrix of n,K holds (- M1) @ = - (M1 @)
let M1 be Matrix of n,K; :: thesis: (- M1) @ = - (M1 @)
for i, j being Nat st [i,j] in Indices ((- M1) @) holds
((- M1) @) * (i,j) = (- (M1 @)) * (i,j)
proof
let i, j be Nat; :: thesis: ( [i,j] in Indices ((- M1) @) implies ((- M1) @) * (i,j) = (- (M1 @)) * (i,j) )
assume A1: [i,j] in Indices ((- M1) @) ; :: thesis: ((- M1) @) * (i,j) = (- (M1 @)) * (i,j)
then A2: [i,j] in Indices (M1 @) by MATRIX_0:26;
[i,j] in [:(Seg n),(Seg n):] by ;
then ( i in Seg n & j in Seg n ) by ZFMISC_1:87;
then A3: [j,i] in [:(Seg n),(Seg n):] by ZFMISC_1:87;
then A4: [j,i] in Indices M1 by MATRIX_0:24;
[j,i] in Indices (- M1) by ;
then ((- M1) @) * (i,j) = (- M1) * (j,i) by MATRIX_0:def 6
.= - (M1 * (j,i)) by
.= - ((M1 @) * (i,j)) by
.= (- (M1 @)) * (i,j) by ;
hence ((- M1) @) * (i,j) = (- (M1 @)) * (i,j) ; :: thesis: verum
end;
hence (- M1) @ = - (M1 @) by MATRIX_0:27; :: thesis: verum